A Descriptive Study on Students’ Difficulties in Learning Vocabulary at the Eighth Grade of SMP Negeri 5 Natar - Putri, Silvia Anisa; Rohmatillah, Rohmatillah; Kholid, M. Fikri Nugraha (Raden Intan State Islamic University of Lampung, Indonesia, 2024)
Vocabulary is one of the components of mastering English as a foreign language. Before students study English skills, they should learn about vocabulary as the first step. Based on the preliminary research, showed that the students still faced difficulties in learning vocabulary namely not knowing the meaning of words, not knowing how to pronounce words, and the written words and how to pronounce the words are not the same. This research only focused on students' difficulties in learning vocabulary and factors that cause students' difficulties in learning vocabulary. Descriptive qualitative research design was employed in this research. Purposive sampling was used in this research. The eighth grade of E was taken as a sample because they had lower scores in vocabulary than other classes. The researcher used questionnaires and interviews to collect the data. The questionnaire was used to find out students’ difficulties in learning vocabulary and the interview was used to find out the factors that cause students’ difficulties in learning vocabulary. The three major phases of data analysis are data condensation, data display, and conclusion drawing. After analyzing the data, the results of the questionnaire showed that there were three difficulties for students in learning vocabulary. The difficulty faced by the students in learning vocabulary was the pronunciation, grammar, and meaning. Based on the students’ interviews, there are three difficulties factors in learning vocabulary. The difficulty factors faced by the students in learning vocabulary was students reluctant to open dictionaries, students less motivation, and students have difficulty concentrating